Sobre el estado electro-tónico y su interpretación: el potencial vectorial - Rozo-Clavijo, Mauricio; Ávila-Torres, Sandra; Walteros-Rodríguez, Angélica (Revista Científica, 2015)
An analysis is presented on the emerging perspectives about the vector potential from Faraday and Maxwell’s original writings. This paper presents the initial observations about the experiments and explanations developed by Faraday on Magnetic Induction and the influence that his concept of Electrotonic State had on Maxwell’s first explanation. He defined it as the state by which magnetic actions are executed through lines of force. He pointed out that this concept is critical to explain the phenomenon of Magnetic Induction in non-Newtonian terms. Therefore, he formalized it by the circulation of vector potential throughout a closed trajectory. This kind of analysis shows how these researchers represented the phenomenon which is not evident in the literature. It’s presented as a formalization around the magnetic field instead.